2003
DOI: 10.1590/s1020-49892003000700005
|View full text |Cite
|
Sign up to set email alerts
|

Estudio neuroepidemiológico nacional (EPINEURO) colombiano

Abstract: These results make it possible to design more up-to-date health policies aimed at achieving more effective prevention, better control, and more adequate treatment of neurological disorders in Colombia. The easy application of these surveys and the low cost of this type of research make this methodology ideal for countries with shortages of specialized personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
53

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 22 publications
1
37
0
53
Order By: Relevance
“…23 En el ENN se seleccionaron al azar tres barrios de Bucaramanga, de estratos socioeconómicos bajo, medio y alto. Se actualizó el mapa cartográfico de cada barrio seleccionado y en cada uno se escogió al azar un núme-ro predeterminado de manzanas y viviendas.…”
Section: Materials Y Métodosunclassified
“…23 En el ENN se seleccionaron al azar tres barrios de Bucaramanga, de estratos socioeconómicos bajo, medio y alto. Se actualizó el mapa cartográfico de cada barrio seleccionado y en cada uno se escogió al azar un núme-ro predeterminado de manzanas y viviendas.…”
Section: Materials Y Métodosunclassified
“…En Colombia la epilepsia es una de la enfermedades neurológicas más frecuentes, con prevalencia de 10,3 por cada 1.000 habitantes (2,3), así que políticas en salud como las descritas en la Resolución 1448 del 8 de mayo de 2006 motivan el desarrollo de nuevas tecnologías que permitan intercambiar datos con el propósito de facilitar el acceso de la población a servicios que presentan limitaciones de oferta, o ambos, en las diversas áreas geográficas (4).…”
Section: Introductionunclassified
“…The most recent is from the midnineties, EPINEURO, a neuro-epidemiologic baseline study, reported a prevalence of 4.7 (IC95%: 2.2 to 8.9) [13]. Accordingly, it is necessary to identify the use of LP in the PD's treatment and to determine the pharmacoeconomic studies' quality that has been done in the last five years.…”
Section: Introductionmentioning
confidence: 99%